Evolución de ingresos y su relación con la evolución de la utilidad en la empresa Leche Gloria S.A. periodo 2019 – 2023 - Sifuentes Loo, Ofelia (2025)
The dairy sector is key to achieving the Sustainable Development Goals (SDGs), but the COVID-19 pandemic accelerated a structural change that was already underway in this sector. There was variability in the impact of the pandemic between different countries, and the considerable structural adjustment that was taking place was highlighted. This study aims to identify the relationship between the evolution of income and the evolution of profit in the company Leche Gloria S.A. for the period 2019 - 2023 at a correlational level and from a quantitative observational approach, identifying that between 2019 and 2023 there is a significant and positive relationship between the evolution of income and the evolution of profit in the company Leche Gloria S.A. for the period 2019 - 2023. The research concludes that the analysis of the evolution of income and profit in Leche Gloria S.A. During the 2019-2023 period, it revealed that, although income has shown constant growth, this has not had a statistically significant relationship with profit; as for gross profit, it presented a moderate positive correlation, but without statistical significance, as well as with profit. Likewise, total income increased from S/ 3,463,414 thousand in 2019 to S/ 4,199,996 thousand in 2023, which represents a growth of 21.27% in five years. However, the profit for the year has not followed the same trend, as it went from S/ 146,517 thousand in 2019 to S/ 170,662 thousand in 2023, with notable fluctuations in the intervening years, especially in 2022 when it fell to S/ 147,133 thousand.